2007
DOI: 10.3766/jaaa.18.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Divided-Attention and Directed-Attention Listening Modes in Children with Dichotic Deficits: An Event-Related Potential Study

Abstract: Dichotic listening (DL) procedures are commonly employed in the evaluation of auditory processing in children. Review of the various clinical tests reveals considerable diversity in both the signals employed and their mode of administration. The extent to which other non auditory-specific factors influence the test outcome is often difficult to determine. Individual differences in memory, attention, facility with test stimuli, and report strategy are always of potential concern in the interpretation of results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 61 publications
1
24
0
Order By: Relevance
“…Such a competition for attention among multiple auditory objects could account for the reduced LPC amplitude. This interpretation is consistent with prior studies showing a reduced LPC under the influence of competitive interference between concurrent stimuli (Martin, Jerger, & Mehta, 2007;Fischler & Bradley, 2006). This phenomenon is also consistent with Wicken's attentional resource model in which attention is divided among mental operations, which impairs performance task demands (Wickens, 1976(Wickens, , 2008.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Such a competition for attention among multiple auditory objects could account for the reduced LPC amplitude. This interpretation is consistent with prior studies showing a reduced LPC under the influence of competitive interference between concurrent stimuli (Martin, Jerger, & Mehta, 2007;Fischler & Bradley, 2006). This phenomenon is also consistent with Wicken's attentional resource model in which attention is divided among mental operations, which impairs performance task demands (Wickens, 1976(Wickens, , 2008.…”
Section: Discussionsupporting
confidence: 88%
“…The participants might have adopted the strategy to keep their attention focused on the tuned harmonic. Previous findings have shown that the LPC amplitude was greater in conditions where participants were asked to focus their attention to a particular stimulus than in conditions where focused attention to that particular stimulus was not required in active listening tasks (Martin et al, 2007). To verify this possibility, future studies may consider comparing LPC amplitudes during gap detection, with the gap having equal probability of being inserted in the tuned and mistuned components of a sound complex.…”
Section: Discussionmentioning
confidence: 94%
“…The middle latency response, from approximately 12 ms to 50 ms poststimulus onset, is probably generated by the upper brainstem and primary auditory cortex and is followed by "later" cortical responses 50-250 ms after stimulus onset (Hall, 1992). Both ABRs and cortical responses have been used in investigations of auditory processing in children with APD, SLI, and dyslexia (e.g., Basu, Krishnan, & Weber-Fox, 2010;Bishop & McArthur, 2005;Jerger, Martin, & McColl, 2004;Jirsa, 1992;Jirsa & Clontz, 1990;Marler & Champlin, 2005;Martin, Jerger, & Mehta, 2007;McArthur, Atkinson, & Ellis, 2009;Sharma et al, 2006).…”
Section: Neurophysiological Methodsmentioning
confidence: 99%
“…Word stimuli were selected from a larger body of words used in a previous study (Martin et al, 2007). The speech stimuli were recorded in an audiometric sound-treated room by an adult male, monolingual speaker of English.…”
Section: Production and Presentation Of Speech Stimulimentioning
confidence: 99%